Analisis Perangkat Pembelajaran IPS Menggunakan Pendekatan Kontekstual Untuk Meningkatkan Aktivitas Belajar Siswa - Agnes Remi Rando; Agustina Pali (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
This research is a development research that aims to describe the development of social studies learning devices using a contextual approach in the fourth grade of the Roworeke 2 Catholic elementary school. The research model used is 4-D development which is reduced to 3-D, namely define, design, and develop. The learning devices developed include lesson plans and student worksheets which were tested in class IV B as a test class consisting of 25 students, and class IV A as a control class consisting of 26 students at Roworeke 2 Catholic Elementary School. The research instrument consisted of an observation sheet on the implementation of learning, an observation sheet for student learning activities and a student response questionnaire sheet. Data was collected using interview, observation, and questionnaire techniques. The implementation of social studies learning using a contextual approach in the experimental class using the observation sheet instrument showed that the teacher's ability to carry out social studies learning on historical heritage materials using a contextual approach was 73% and was stated to be well implemented. While the analysis of the results of student learning activities using social studies learning devices with a contextual approach and lecture method as follows: experimental class activity I 65% and control class 31%, while activity II 65% in the experimental class and 35% in the control class. So it can be concluded that the activity in the experimental class is better (active category) than the activity in the control class.